Pembelajaran Bahasa Inggris Berbasis Lagu untuk Menciptakan Suasana Belajar yang Menyenangkan - Josafat Christopher; Nuri Kaerani Kamil; Selly Nuraini; Sri Mulyeni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Learning English as a Foreign Language English as a Foreign Language still faces various linguistic and psychological challenges, both in school-age and adult learners, such as limited vocabulary mastery, pronunciation difficulties, and low confidence in the use of English orally. This condition is exacerbated by affective factors in the form of anxiety and fear of making mistakes. This article aims to examine the use of songs as a learning medium that is able to create a fun learning atmosphere, while improving learners' English skills. This study uses a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews to explore learners' perceptions and experiences related to the effectiveness of songs in English language learning. Meanwhile, the data were analyzed thematically to identify patterns of learning experiences, especially in terms of vocabulary mastery, classroom atmosphere, and confidence level. The results showed that the integration of songs in English learning was highly motivating in the active involvement of learners. Where the repetition of lyrics combined with melodies helps to strengthen vocabulary retention in long-term memory, as well as facilitate the imitation of pronunciation, intonation, and rhythm of language naturally. At the same time, it creates a relaxed and fun learning atmosphere, thereby lowering psychological barriers as described in the Affective Filter Hypothesis. Thus, songs are an integrative learning medium that is effective in bridging the academic needs and emotional comfort of learners, and is relevant to support the development of listening and speaking skills in English learning across ages.